2023
DOI: 10.3390/ijerph20115930
|View full text |Cite
|
Sign up to set email alerts
|

Association between Physical Fitness and Cardiovascular Health in Firefighters

Abstract: Firefighters perform strenuous work in dangerous and unpredictable environments requiring optimal physical conditioning. The aim of this study was to investigate the association between physical fitness and cardiovascular health (CVH) in firefighters. This cross-sectional study systematically recruited 309 full-time male and female firefighters between the ages of 20 to 65 years in Cape Town, South Africa. Physical fitness was assessed using absolute (abV̇O2max) and relative oxygen consumption (relVO2max), gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Similarly, other adolescents and adults who improved cardiorespiratory fitness and muscular strength were more likely to maintain adequate blood pressure levels 37 . Likewise, the study by Ras et al 38 suggests that higher VO2max is associated with lower blood pressure and greater abdominal repetitions. Similar findings were observed according to Correa-Rodríguez et al 39 , lower strength in dynamometry was associated with increased cardiometabolic risk probabilities and higher blood pressure.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, other adolescents and adults who improved cardiorespiratory fitness and muscular strength were more likely to maintain adequate blood pressure levels 37 . Likewise, the study by Ras et al 38 suggests that higher VO2max is associated with lower blood pressure and greater abdominal repetitions. Similar findings were observed according to Correa-Rodríguez et al 39 , lower strength in dynamometry was associated with increased cardiometabolic risk probabilities and higher blood pressure.…”
Section: Discussionmentioning
confidence: 93%
“…Body mass and Lean body mass (LBM) was used as a measure for body composition and assessed using a bioelectrical impedance (BIA) analyser (Tanita© BC-1000 Plus BIA scale). For a full description of the methods used to assess physical fitness consult the study published by: Ras et al [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, age was inversely related to maximal oxygen consumption, number of push-ups, sit-up repetitions, and flexibility [16]. Concurrently, a negative correlation was observed between body fat percentage and absolute maximal oxygen consumption, leg strength, handgrip strength, the count of push-up and sit-up repetitions performed, and lean body mass [16]. Comparable results were documented in a study of Spanish firefighters, which identified age, weight, and total body fat as significant predictors of maximal oxygen consumption, with total body fat being identified as the most significant predictor [17].…”
Section: Introductionmentioning
confidence: 98%
“…Low cardiorespiratory fitness has been identified as a contributory factor towards the onset of health problems such as obesity, hypertension, and heart disease, all of which are increasing with advanced age [15]. Moreover, research conducted by Ras et al (2023) investigating the relationship between physical fitness and cardiovascular well-being in firefighters revealed that poor cardiovascular health was negatively associated with relative oxygen consumption, leg strength, and the count of push-up repetitions [16]. In addition, age was inversely related to maximal oxygen consumption, number of push-ups, sit-up repetitions, and flexibility [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation